Deficiency of prion protein induces impaired autophagic flux in neurons - Shin, Hae-Young; Park, Jeong-Ho; Carp, Richard I.; Choi, Eun-Kyoung; Kim, Yong-Sun (Frontiers in Aging Neuroscience, 2014)
Normal cellular prion protein (PrPC) is highly expressed in the central nervous system. The Zürich I Prnp-deficient mouse strain did not show an abnormal phenotype in initial studies, however, in later studies, deficits in exploratory behavior and short- and long-term memory have been revealed. In the present study, numerous autophagic vacuoles were found in neurons from Zürich I Prnp-deficient mice. The autophagic accumulation in the soma of cortical neurons in Zürich I Prnp-deficient mice was observed as early as 3 months of age, and in the hippocampal neurons at 6 months of age. Specifically, there is accumulation of electron dense pigments associated with autophagy in the neurons of Zürich I Prnp-deficient mice. Furthermore, autophagic accumulations were observed as early as 3 months of age in the CA3 region of hippocampal and cerebral cortical neuropils. The autophagic vacuoles increased with age in the hippocampus of Zürich I Prnp-deficient mice at a faster rate and to a greater extent than in normal C57BL/6J mice, whereas the cortex exhibited high levels that were maintained from 3 months old in Zürich I Prnp-deficient mice. The pigmented autophagic accumulation is due to the incompletely digested material from autophagic vacuoles. Furthermore, a deficiency in PrPC may disrupt the autophagic flux by inhibiting autophagosome-lysosomal fusion. Overall, our results provide insight into the protective role of PrPC in neurons, which may play a role in normal behavior and other brain functions.